2016
DOI: 10.1212/nxi.0000000000000211
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl fumarate treatment of relapsing-remitting multiple sclerosis influences B-cell subsets

Abstract: Objective:To test the hypothesis that dimethyl fumarate (Tecfidera, BG-12) affects B-cell subsets in patients with relapsing-remitting multiple sclerosis (RRMS).Methods:Peripheral blood B cells were compared for surface marker expression in patients with RRMS prior to initiation of treatment, after 4–6 months, and at more than 1 year of treatment with BG-12. Production of interleukin (IL)–10 by RRMS patient B cells was also analyzed.Results:Total numbers of peripheral blood B lymphocytes declined after 4–6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 40 publications
11
69
0
Order By: Relevance
“…This cross-sectional study demonstrates that while DMF-treatment causes a time-dependent reduction in CD19 + CD27 + CD38memory B cells in blood, it leads to a depletion of CD19 + CD27 + CD38 + plasmablasts in the CSF. Our findings in blood are in agreement with recent publications [13][14][15][16] , and the present work demonstrates how the peripheral effects of DMF translate into the CSF. These data point to a possible B-cell mediated mechanism of action for DMF, in addition to the previously discussed pluripotent immunomodulatory effects 12 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This cross-sectional study demonstrates that while DMF-treatment causes a time-dependent reduction in CD19 + CD27 + CD38memory B cells in blood, it leads to a depletion of CD19 + CD27 + CD38 + plasmablasts in the CSF. Our findings in blood are in agreement with recent publications [13][14][15][16] , and the present work demonstrates how the peripheral effects of DMF translate into the CSF. These data point to a possible B-cell mediated mechanism of action for DMF, in addition to the previously discussed pluripotent immunomodulatory effects 12 .…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have shown that DMF reduces the number of memory B cells in blood [13][14][15][16] , typically identified as CD19 + CD27 + cells. To identify these cells in blood and CSF, a gating strategy based on available data was devised ( Figure 1).…”
Section: Dmf Reduces the Frequency Of Memory B Cells In Blood And Plamentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, NK-like T cells (NKT), identified as FSC low CD14 - TCRαβ + CD56 + , were progressively decreased and the differences were significant between the long term >18M treatment group and the untreated group ( P =0.0007). B cell counts were significantly decreased after >18 months of treatment and the detailed B cell subtype changes were described in our recent paper (14). Total NK cell counts showed no significant differences among the three groups.…”
Section: Resultssupporting
confidence: 58%
“…The effectiveness of DMF in psoriasis also suggests an immune regulatory role, which prompted us to study the effects of DMF treatment on human peripheral lymphocytes in DMF-treated RRMS patients. We recently reported that RRMS patients treated with DMF had reduced levels of naïve and memory B cells, while there was an increase in B cells with phenotypes reported to produce IL-10 and to have regulatory capacity (14). Rare cases of progressive multifocal leukoencephalopathy (PML) have been reported to be associated with long-term DMF treatment of psoriasis and MS patients (15-18), which make it important to understand the immunological changes induced by DMF treatment in order to find reliable biomarker(s) that can predict JC virus activation and prevent PML.…”
Section: Introductionmentioning
confidence: 99%